Analyse de la contribution des infrastructures en matière de réduction de la pauvreté : cas du Bénin - MEDJIGBODO, ROLAND MARIE-PIÈRRE (My University, 2008)
The multidimensional character of poverty requires going beyond the monetary aspect, which is insufficient to deal with poverty on whole. The availability and accessibility of public services is a major point in this approach. These services are in general provided by the infrastructures. The development of the infrastructures could be appreciated from the point of view of the quantity, quality, cost and equality of access. To generalize access to the public services generated by infrastructures, for rural populations in particular, we need at the same time innovative resources and methods. It is essential then to make inventory of the infrastructures so as to give an account of effectiveness of the policies initiated in order to fight for the reduction of poverty Keywords: poverty, infrastructures, public services, multidimensional analysis. JEL classification: H5, I1, I2, I3
Keywords: Pauvreté; analyse multidimensionnelle; infrastructure; services publics